Complex Systems Design & Management Proceedings of the Ninth International Conference on Complex Systems Design & Management, CSD&M Paris 2018 - Bonjour, Eric; Krob, Daniel; Palladino, Luca; Stephan, François (Springer International Publishing : Imprint: Springer, 2019)
This book contains all refereed papers accepted during the ninth edition of the conference that took place at the Cité Internationale Universitaire de Paris on December 18-19, 2018. Mastering complex systems requires an integrated understanding of industrial practices as well as sophisticated theoretical techniques and tools. This explains the creation of an annual go-between forum in Paris dedicated to academic researchers & industrial actors working on complex industrial systems architecture, modeling & engineering. These proceedings cover the most recent trends in the emerging field of Complex Systems, both from an academic and a professional perspective. A special focus is put on "Products & services development in a digital world". The CSD&M Paris 2018 conference is organized under the guidance of CESAM Community (http://cesam.community/en). CESAM Community has been developed since 2010 by the non-profit organization CESAMES Association to organize the sharing of good practices in Enterprise and Systems Architecture and to certify the level of knowledge and proficiency in this field through CESAM certification.